2019
DOI: 10.1002/hed.25600
|View full text |Cite
|
Sign up to set email alerts
|

Detection of laryngeal carcinoma in the U.S. elderly population with gastroesophageal reflux disease

Abstract: Background An association is suggested between gastroesophageal reflux disease (GERD) or laryngopharyngeal reflux (LPR) and malignancy of the larynx in elderly patients in the United States. Early detection with flexible fiberoptic laryngoscopy (FFL) or CT remains poorly defined. Methods The Surveillance, Epidemiology, and End Results (SEER)‐Medicare linked database was queried from 2003 to 2011.A case‐cohort design evaluated patients aged 66 and older with a diagnosis of GERD and/or LPR for the occurrence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Recent studies have suggested associations between chronic inflammatory conditions of the head and neck such as chronic sinusitis and gastroesophageal reflux and the development of malignancy of the upper aerodigestive tract (UADT). 9-13 There is a perceived assumption that ETD in an elderly population is largely associated with the presence of UADT malignancy or a result of the treatments for UADT malignancy, but there are little data directly comparing these populations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have suggested associations between chronic inflammatory conditions of the head and neck such as chronic sinusitis and gastroesophageal reflux and the development of malignancy of the upper aerodigestive tract (UADT). 9-13 There is a perceived assumption that ETD in an elderly population is largely associated with the presence of UADT malignancy or a result of the treatments for UADT malignancy, but there are little data directly comparing these populations.…”
mentioning
confidence: 99%
“…In adults, ETD can occur in isolation or in association with a number of inflammatory disorders of the aerodigestive tract, 8 although these associations remain incompletely characterized, particularly in the elderly population. Recent studies have suggested associations between chronic inflammatory conditions of the head and neck such as chronic sinusitis and gastroesophageal reflux and the development of malignancy of the upper aerodigestive tract (UADT) 9–13 . There is a perceived assumption that ETD in an elderly population is largely associated with the presence of UADT malignancy or a result of the treatments for UADT malignancy, but there are little data directly comparing these populations.…”
mentioning
confidence: 99%
“…El-Serag et al [35] concluded that gastroesophageal reflux or LPR increased the risk of laryngeal carcinoma. Some studies also demonstrated that LPRD or GERD was a risk factor for laryngeal and hypopharyngeal carcinoma after adjusting for factors such as smoking and drinking in multivariate logistic regression analysis [19,26,27,36]. In a systematic review and meta-analysis, Parsel et al [20] found a significant correlation between LPRD and laryngeal malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this review uses both terms (LPRD and GERD). There is increasing interest in whether LPRD can induce chronic damage and inflammation of the laryngeal and pharyngeal mucosae, and whether LPRD can induce a final tumorigenic effect on laryngeal and pharyngeal mucosae [17][18][19][20][21][22][23][24][25][26][27][28][29]. However, the effects of GERD or LPRD on laryngeal and hypopharyngeal carcinomas remain controversial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation